2021
DOI: 10.5194/bg-18-5699-2021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atmospheric deposition on biogeochemical cycles in an oligotrophic ocean system

Abstract: Abstract. The surface mixed layer (ML) in the Mediterranean Sea is a well-stratified domain characterized by low macronutrients and low chlorophyll content for almost 6 months of the year. In this study we characterize the biogeochemical cycling of nitrogen (N) in the ML by analyzing simultaneous in situ measurements of atmospheric deposition, nutrients in seawater, hydrological conditions, primary production, heterotrophic prokaryotic production, N2 fixation and leucine aminopeptidase activity. Dry deposition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Few studies have considered the importance of the aerosol deposition pathway, either through dust storms (dry deposition) or rainfall events (wet deposition; Ridame et al 2014; Van Wambeke et al 2021), despite them potentially differing in terms of aerosol acidity (lower pH under wet deposition) and settling efficiency in the air (elevated under wet deposition), which is expected to have a critical impact on the magnitude of nutrient supply (Baker et al 2007, 2010; Jung et al 2011). In addition, we know comparatively little about how aerosol deposition affects specific phytoplankton groups (DiTullio and Laws 1991; Kramer et al 2020), despite this potentially having important implications for carbon export; for instance, phytoplankton blooms dominated by diatoms are more likely to trigger enhanced export of faster‐sinking particulate organic carbon to the ocean interior (Martin et al 2011; Leblanc et al 2018).…”
mentioning
confidence: 99%
“…Few studies have considered the importance of the aerosol deposition pathway, either through dust storms (dry deposition) or rainfall events (wet deposition; Ridame et al 2014; Van Wambeke et al 2021), despite them potentially differing in terms of aerosol acidity (lower pH under wet deposition) and settling efficiency in the air (elevated under wet deposition), which is expected to have a critical impact on the magnitude of nutrient supply (Baker et al 2007, 2010; Jung et al 2011). In addition, we know comparatively little about how aerosol deposition affects specific phytoplankton groups (DiTullio and Laws 1991; Kramer et al 2020), despite this potentially having important implications for carbon export; for instance, phytoplankton blooms dominated by diatoms are more likely to trigger enhanced export of faster‐sinking particulate organic carbon to the ocean interior (Martin et al 2011; Leblanc et al 2018).…”
mentioning
confidence: 99%
“…Parallel nutrient enrichment incubations conducted in darkness showed that in situ heterotrophic bacterioplankton communities (initial conditions of the present experiments) were N, P co-limited at TYR, mainly P limited at ION, and N limited at FAST (Van Wambeke et al, 2021). However, after incubation, the HB appeared to be weakly bottom-up controlled (Ducklow, 1992) especially in D and G (Fig.…”
Section: Trophic Interactions After Dust Addition Under Present and F...mentioning
confidence: 54%
“…Intriguingly, the enhanced viral production did not translate into marked changes in the viral abundance. The abundance of a low DNA virus population, which typically comprises the viruses of bacteria, actually decreased between t0 and t48h pointing to a possible viral decay, potentially related to an adsorption onto dust particles (Weinbauer et al, 2009;Yamada et al, 2020) and the potential export of viral particle to deeper water layers (Van Wambeke et al, 2021). While recurrent patterns emerged from this study, the amplitude of viral responses varied between the experiments.…”
Section: Viral Processes and Community During Dust Enrichment In Pres...mentioning
confidence: 62%
See 1 more Smart Citation
“…This estimate is much higher than in the surface and mid‐layer waters of the offshore area (9%) and river mouth (11%), and slightly higher than in the high‐salinity water of PRE (17%) during the winter (Ye et al., 2016), manifesting the importance of atmospheric nitrate deposition to the offshore ecosystem. Although the atmospheric nitrate may be rapidly assimilated and cycled at the surface, particularly in the oligotrophic areas (Tsunogai et al., 2011; Van Wambeke et al., 2021). However, in our study area in the PRE, the nutrients in the water column are relatively sufficient, particularly ammonium; even the average concentration of NH 4 + in the surface water of the nearshore and offshore area can still reach 1.33 μmol/L (Figure 2).…”
Section: Discussionmentioning
confidence: 99%